Menumbuhkembangkan Budaya Kewirausahaan dalam Masyarakat - Jonnius Jonnius (Lembaga penelitian dan pengabdian kepada masyrakat, 2013)
Currently, the field of entrepreneurship is still not a top choice as a profession in Indonesian society, so it is still underdeveloped compared to developed countries. Entrepreneurial culture should be fostered in the community as early as possible starting from the family environment and the environment closest to the formal educational institutions ranging from elementary school through college. Entrepreneurial activity must be enabled in lingkkungan society that can be observed directly. This activity will be the habit of the community so that it becomes a learning process that will form habits/culture. In order to serve as an entrepreneurial culture, then this practice should be owned in common by way of involving all the components that exist in society. Party government as the main actors in this movement may involve the intellectual as the originator of the ideas/good ideas in the development of the entrepreneurship program itself as well as in the development of technology and information that is useful in the world of business undertaken by community entrepreneurs (entrepreneurs). People are more encouraged to start a business or businesses in both small and large scale. The attitude of risk-taking must be invested in order to various business plan is realized. Starting a homebased business venture is also a smart idea, as it has a distinct advantage, especially in the early and minimize operating costs.